2006
DOI: 10.1016/j.compfluid.2005.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Numerical dissipation and the bottleneck effect in simulations of compressible isotropic turbulence

Abstract: Energy spectrum functions computed from data of various three-dimensional simulations of forced isotropic turbulence are investigated. The piece-wise parabolic method (PPM) was used to treat flows with Mach number of the order unity. The dissipation is of purely numerical origin. For the dimensionless mean rate of dissipation, we find values in agreement with results from other, mostly incompressible turbulence simulations. The so-called bottleneck phenomenon is also present in the turbulence energy spectra. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 31 publications
4
105
0
Order By: Relevance
“…At later times (t = 0.31 t cross , and t = 0.62 t cross ) all codes produced similar density-weighted power spectra for k 20, while the ENZO code develops a clear bottleneck (see e.g. Dobler et al 2003;Haugen & Brandenburg 2004;Schmidt et al 2006a), which manifests itself in the excess power seen at k 10. Since ENZO was run here with a PPM diffusion parameter set to K = 0.0 (Colella & Woodward 1984), the bottleneck effect is quite strong (see also Kritsuk et al 2007;Federrath et al 2009a).…”
Section: Volume-weighted and Density-weighted Velocity Power Spectramentioning
confidence: 96%
See 1 more Smart Citation
“…At later times (t = 0.31 t cross , and t = 0.62 t cross ) all codes produced similar density-weighted power spectra for k 20, while the ENZO code develops a clear bottleneck (see e.g. Dobler et al 2003;Haugen & Brandenburg 2004;Schmidt et al 2006a), which manifests itself in the excess power seen at k 10. Since ENZO was run here with a PPM diffusion parameter set to K = 0.0 (Colella & Woodward 1984), the bottleneck effect is quite strong (see also Kritsuk et al 2007;Federrath et al 2009a).…”
Section: Volume-weighted and Density-weighted Velocity Power Spectramentioning
confidence: 96%
“…Schmidt et al (2006a) suggested that the bottleneck peaks at k ∼ N/10 ∼ 26. These authors also argued that, in codes showing no bottleneck, numerical dissipation will start acting at wavenumbers smaller than k ∼ N/10.…”
Section: Volume-weighted Velocity Power Spectrum Of the Initial Condimentioning
confidence: 99%
“…The turbulent energy is continuously injected by a specific force f on length scales corresponding to wavenumbers 1 < k < 3, where k is normalised by 2π/X for a box of size X. Each component of this force is modelled by an OrnsteinUhlenbeck process (Eswaran & Pope 1988;Schmidt et al 2006Schmidt et al , 2009Federrath et al 2010b). We define the integral scale L by the mean wavelength of the forcing, i.e., L = X/2.…”
Section: Introductionmentioning
confidence: 99%
“…We emphasise that this scaling range was chosen very carefully, since turbulence simulations will only provide a small inertial range even at resolutions of 1024 3 grid cells (see, e.g., Klein et al 2007;Lemaster & Stone 2009). This is mainly caused by the bottleneck phenomenon (e.g., Porter et al 1994;Dobler et al 2003;Haugen & Brandenburg 2004;Schmidt et al 2006;Kritsuk et al 2007), which may slightly affect the Fourier spectra in the dissipation range. However, the bottleneck phenomenon had no significant impact on the turbulence statistics in our numerical study for wavenumbers k < ∼ 40.…”
Section: Velocity Fourier Spectramentioning
confidence: 99%
“…The OU process is a well-defined stochastic process with a finite autocorrelation timescale. It can be used to excite turbulent motions in 3D, 2D, and 1D simulations as explained in Eswaran & Pope (1988) and Schmidt et al (2006). Using an OU process enables us to control the autocorrelation timescale T of the forcing.…”
Section: Forcing Modulementioning
confidence: 99%